Creating Inclusive Teams Through Perceptions of Supplementary and Complementary Person–Team Fit: Examining the Relationship Between Person–Team Fit and Team Effectiveness. (June 2016) - De Cooman, Rein; Vantilborgh, Tim; Bal, Matthijs; Lub, Xander
Using a multi-wave, multi-level design, this study unravels the impact of subjective (dis)similarities in teams on team effectiveness. Based on optimal distinctiveness theory and the social inclusion model, we assume combined effects of individual and shared perceptions of supplementary and complementary person–team fit on affective and performance-based outcomes. Furthermore, at the team level, we expect this relationship to be mediated by team cohesion. In a sample of 121 participants (across 30 teams), we found that teams in which members share perceptions of high supplementary as well as high complementary fit outperform those in which they do not. In addition, members of such teams report higher levels of team satisfaction and viability. Both of these occur through positive effects on the cohesion within the team. Thereby, our results support the central tenet of the social inclusion model. At the individual level, this enhancing effect of the interaction was not supported, providing additional evidence for considering perceived person–team fit as a collective construct.